Pendidikan Gizi Sarapan Sehat dan Praktik Cuci Tangan Pada Siswa Sekolah Dasar - Taufiq Firdaus Alghifari Atmadja; Kosasih Adi Saputra (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
Clean and healthy behavior (CHB) is one of the activities to change unhealthy behaviors into healthy ones. PHBS should be applied early, especially in school-age children by getting a healthy breakfast and washing hands. The benefits of breakfast include being a source of energy so as to prevent students from consuming unhealthy snacks, besides washing hands before or after the activity is also an important thing that needs to be accustomed early on. The purpose of this activity is to increase students' knowledge about PHBS through healthy breakfast education and good hand washing. The method used in this activity is education through powerpoint and poster media. This activity was attended by 6th grade students at SDN 1 Ciawi and SDN 2 Ciawi in Tasikmalaya Regency, West Java, with a total number of 80 students. Before and after the delivery of material students are given questions to see the level of success of this activity. Based on the results of the evaluation showed that an increase in student knowledge is expected to be able to increase students' understanding of healthy breakfast and good hand washing